The effect of magnetic treatment on some physical properties of Seawater1 - Mohammed, Seham; Mansouri, Rasha (Libyan Journal of Science &Technology, 2022)
The effect of the magnetic field (14500 Gauss or 1.45 T) on density, electrical conductivity, and viscosity of seawater concentrations (20, 50, and 80%) is studied here. The results show that magnetic treatment causes a significant increase in the density and electrical conductivity of seawater, while the viscosity is decreased as compared to the ordinary seawater without magnetic treatment. The experiment was carried out during the winter of 2019, at the laboratory of physics, College of Sciences, Ajdabiya University, Libya.